USING PEER COLLABORATION TECHNIQUE TO IMPROVE STUDENTS' WRITING SKILL OF THE EIGHT GRADE OF SMP NEGERI 1 TONRA - Said, Dian Riani; Muhdar, Fahriadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Abstrack : The objective of this study to know the difference of students writing ability before and after being thought by related picture. Pre-experimental method was to find applied in this research with one sample group and two test, pre-test and pos-test. The population of this research was basic writing class VIII in SMP Negeri 1 Tonra Subdistrict of Tonra Bone Regency 2018-2019. The total sample of this research was 21 students from one class. Whereas, the result of computation showed that t-observed was 9,71 and t-critical was 2.086 (at 1c.=0.05). It meant that t observed was higher than t-critic (9,71 > 2.086). Thus, the null hypothesis was rejected, and the alternative hypothesis was accepted. It meant that there was a significant difference in students' writing ability before and after being taught by using related pictures. So it could be concluded that teaching writing by using related pictures gave better result in improving the students' writing ability of descriptive genre. There is a significant difference eight grade in students' of SMP Negeri 1 Tonra Subdistrict of Tonra Bone Regency writing ability before and after being taught by using related pictures.